PEMBERDAYAAN KELOMPOK SADAR WISATA (POKDARWIS) OLEH DINAS PARIWISATA KEBUDAYAAN KEPEMUDAAN DAN OLAHRAGA KABUPATEN SUMEDANG - Nurlaelasari, Meli (LPPM UNSAP & FISIP UNSAP, 2025)
This study aims to determine how the empowerment of tourism awareness groups by the Sumedang Regency Tourism, Culture, Youth and Sports Office. The research method used in this research is qualitative research method. The technique of determining informants is by purposive sampling technique. With informants, namely the Head of the Tourism Division, Staff of the Tourism and Creative Economy Adyatama Section of Young Experts, Chairperson of the Nyalindung Village Tourism Awareness Group, Chairperson of the Gunturmekar Tourism Awareness Group, Chairperson of the Citengah Village Tourism Awareness Group, Chairperson of the Rancamulya Village Tourism Awareness group. The data collection techniques used were literature studies and field studies consisting of observation, interviews, documentation, and triangulation. The data validity techniques used are credibility, transferability, depenability, and confirmability tests. Data analysis techniques in this study are Data collection, Data Reduction, Data Display and Verification. Based on the results of the study, it is concluded that the Empowerment of Tourism Awareness Groups by the Sumedang Regency Tourism, Culture, Youth and Sports Office has not been running optimally because it has not been comprehensive to tourism awareness groups, especially in policy-making participation and has not been carried out regularly. There are obstacles in empowering tourism awareness groups, namely a work environment that is not fully supportive, low community participation, limited funding and human resources, unclear information, and low skills and understanding of members. Efforts to overcome these obstacles are regional structuring, training, monitoring, coaching, imitation studies, cross-sector cooperation, provision of empowerment facilities.